La libertà di informazione al tempo della pandemia. Rilievi critici in margine all’istituzione dell’«unità di monitoraggio per il contrasto della diffusione di fake news relative al CoViD-19 sul web e sui social network» (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
: In the context of the broader debate on measures that affect fundamental freedoms and rights – adopted to deal with the pandemic emergency – the essay analyzes some measures that involve in freedom of information, for health protection purposes. Particular attention is paid to new public unit in charge of develop and promote policy to counter the spread of fake news related to CoViD-19. The analysis aims to highlight the contradictions of a measure aimed at contrasting the «false, unproven or misleading» content conveyed by the web and social networks, and to promote communication from “official sources”. Furthermore, the contribution intends to underline the need and usefulness – precisely with reference to the context determined by the pandemic – to maintain and feed a free and open public debate.
Keywords: CoViD-19; pandemic emergency; fake news; social network; freedom of information